ANALISIS PENGARUH FINANCIAL TECHNOLOGY TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN BUMN DI INDONESIA. - Stenly Jacobus Ferdinandus; Muh Sahril Gunawan Bugis; Josef R. Pattiruhu (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the influence of Financial Technology on the profitability of state-owned banking companies in Indonesia. This research method is a descriptive method with a quantitative approach. The population used is state-owned banks listed on the Indonesia Stock Exchange (IDX). The sampling technique uses the purposive sampling method. To analyze the data, the authors used the SmartPLS 3.0 analysis tool. Based on the results of the research conducted, it can be seen that the four exogenous variables which include mobile banking, internet banking, sms banking and phone banking have a positive effect on endogenous variables which include returns on assets. The results showed that from the variables of mobile banking (X1) and return on assets (Y1) had a significant effect with a signification value of 0.035 (p<0.05), the internet banking variable (X2) on return on assets (Y1) showed significantly with the signification value of 0.048 (p<0.05), the sms banking variable (X3) to the return on assets (Y1) showed significant with a signification value of 0.000 (p<0.05) and the phone banking variable (X4) against the return on assets (Y1) showed significant with the signification value is 0.013 (p<0.05). It is known that the results of the R Square value influence mobile banking, internet banking, sms banking and phone banking on the return on assets of 0.528 or in percentage terms is 52.8% (moderate model).